Some observations on social security and the aged - Elwood, Thomas (Statistical and Social Inquiry Society of Ireland, 1958)
In this necessarily brief survey of the social problems of old age I propose to consider? The nature and extent of the problem due to the changing age structure of the nation; The statutory and non-statutory financial provision made for old age; The provision of accommodation. The first two parts of the subject are considered mainly as they appear in Great Britain, the larger field there providing a better picture of the emerging problems than if Northern Ireland alone were taken, and, further, more specific information is readily available as regards Great Britain. What is said about the general trends and the conclusions to be drawn can, however, be applied to Northern Ireland.
Read before the Society, 30 January 1958
Keywords: Social security; Pensions; Social welfare system; 314.15